2021
DOI: 10.3390/molecules26072009
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Parsley Polyphenols and Their Antioxidant Capacity to Help in the Treatment of Depression and Anxiety: An In Vivo Subacute Study

Abstract: Depression and anxiety are major mental health problems in all parts of the world. These illnesses are associated with a number of risk factors, including oxidative stress. Psychotropic drugs of a chemical nature have demonstrated several side effects that elevated the impact of those illnesses. Faced with this situation, natural products appear to be a promising alternative. The aim of this study was to evaluate the anxiolytic and antidepressant effects of the Petroselinum sativum polyphenols in vivo, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Clinical and pre-clinical trials have reported successful use of medications for certain plant metabolites, such as alkaloids, terpenes, flavonoids, and sterols and others [ 24 , 25 ]. Medicinal plants have also proven efficacy against depression and anxiety, reported with the use of multiple plants, such as Carum carvi polyphenols at doses of 50 and 100 mg/kg [ 26 ], Coriandrum sativum at doses of 50, 100, and 200 mg/kg [ 27 ], Origanum majorana polyphenols at doses of 50 and 100 mg/kg [ 28 ], and Petroselinum sativum at doses of 50 and 100 mg/kg [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and pre-clinical trials have reported successful use of medications for certain plant metabolites, such as alkaloids, terpenes, flavonoids, and sterols and others [ 24 , 25 ]. Medicinal plants have also proven efficacy against depression and anxiety, reported with the use of multiple plants, such as Carum carvi polyphenols at doses of 50 and 100 mg/kg [ 26 ], Coriandrum sativum at doses of 50, 100, and 200 mg/kg [ 27 ], Origanum majorana polyphenols at doses of 50 and 100 mg/kg [ 28 ], and Petroselinum sativum at doses of 50 and 100 mg/kg [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study that concerns the chemical composition of ODSO has shown that it is also rich in phenolic compounds [33]. ese compounds are well known for their antioxidants power, and they are found in many foods and beverages and involved in the prevention of several major chronic illnesses [34,35]. erefore, the nephroprotective effect of ODSO may be related to its free radical trapping effect generated by gentamicin and related to its antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…The chemopreventive effects of parsley leaf oil were demonstrated in a study, and the potential cancer-preventive effects were attributed mainly to the presence of Myristicin [ 30 ]. Various other P. crispum has been reported in studies [ 31 , 32 ]. Myristicin was found to be the principal constituent of PCEO.…”
Section: Resultsmentioning
confidence: 99%